The Effect of Profitability, Liquidity, Investment Opportunity Set, and Company Size on Dividend Policy - Wikan Budi Utami (STIE AAS Surakarta, 2021)
This research aims to determine the simultaneous and partial effect of profitability, liquidity, investment opportunity set and firm size on firm size in Manufacturing Companies on the Indonesia Stock Exchange in 2015-2019. The research method used is quantitative analysis method. The data collection method in this research is the documentation method. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. Purposive sampling method was used in taking research samples. The variables of this research consist of four independent variables, namely X1, Profitability as a proxy for Return On Assets (ROA); X2, Liquidity proxied by Current Ratio (CR; X3, Investment Opportunity Set (IOS) proxied by Market to Book Value of Equity (MBVE) and X4, Company Size (size) as proxied by Ln Net Total Assets Dividend Policy Variable which is proxied by the Dividend Payout Ratio (DPR) as the dependent variable Y. The conclusion in this research is that simultaneously ROA (X1), CR (X2), IOS (X3) and Size (X4) have a significant effect on DPR (Y). only one independent variable, namely CR has a positive and significant effect on DPR, while the ROA, IOS, Size variables have no significant effect on DPR (Y). The coefficient of determination (R2) is 18.5%, which means ROA, CR, IOS, and Size is able to explain the DPR variable by 18.5%, while the remaining 81.5% is explained by other variables other than the variables of this research.